1983
DOI: 10.1037/0735-7028.14.6.882
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of children regarding their participation in psychoeducational decisions.

Abstract: A brief review of literature regarding children's involvement in decision making is presented to illustrate the need for research exploring children's perspectives on their participation in treatment planning. A study is reported in which statements about participation in psychoeducational decision making were elicited from 32 students enrolled in a full-day school program for remediation of learning and behavior problems. As part of regular program planning for the next year, these students were able to choos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…One major focus has been on minors' competence to make major decisions in an informed and effective manner. In this connection, there is an increasing body of research suggesting that many youngsters, even preteenagers and those with psychoeducational problems, are capable of participating competently in decisionmaking forums (e.g., Adelman, Lusk, Alvarez, & Acosta, 1985;De Charms, 1976;Grisso & Vierling, 1978;KaserBoyd, Adelman, & Taylor, 1985;Lewis, Lewis, Lorimer, & Palmer, 1977;Taylor & Adelman, 1986;Taylor, Adelman, & Kaser-Boyd, 1983. As with many areas of performance, however, effective participation depends upon an appropriate match not only between one's skills and the demands of the situation, but also between one's motivation and situational requirements (Hunt, 1961).…”
mentioning
confidence: 97%
“…One major focus has been on minors' competence to make major decisions in an informed and effective manner. In this connection, there is an increasing body of research suggesting that many youngsters, even preteenagers and those with psychoeducational problems, are capable of participating competently in decisionmaking forums (e.g., Adelman, Lusk, Alvarez, & Acosta, 1985;De Charms, 1976;Grisso & Vierling, 1978;KaserBoyd, Adelman, & Taylor, 1985;Lewis, Lewis, Lorimer, & Palmer, 1977;Taylor & Adelman, 1986;Taylor, Adelman, & Kaser-Boyd, 1983. As with many areas of performance, however, effective participation depends upon an appropriate match not only between one's skills and the demands of the situation, but also between one's motivation and situational requirements (Hunt, 1961).…”
mentioning
confidence: 97%
“…Our initial efforts have assessed the degree to which the youngsters actually went to participate in processes affecting their lives and how this affects their behavior. In this connection, we found that the majority value the opportunity to participate in making decisions about school placement and program, that they capably follow through in participating, and that they are interested in learning how to do so more effectively (Taylor, Adelman, & Kaser-Boyd, 1983, 1985a. In contrast, we found the majority reluctant to participate when they were not involved in the decision-making process, such as referral to therapy (Adelman, Kaser-Boyd, Adelman & Taylor, 1986a;,1985b.…”
Section: And (C) Expectations About Accomplishing the Outcomementioning
confidence: 78%
“…Their responses also indicate that they value control at school quite highly. Taken as a whole, their responses to the PCSS and PICSS represent another set of data showing that minors, including those in special education programs, can voice clear perceptions about their sense of control in school and clinical settings (e.g., see Taylor et al, 1983Taylor et al, , 1985aTaylor et al, , 1985b.…”
Section: Discussionmentioning
confidence: 99%
“…Older adolescents display greater commitment to a course of action than early to middle adolescents (Taylor et al, 1983(Taylor et al, , 1985.…”
Section: Commitmentmentioning
confidence: 97%